2016
DOI: 10.7717/peerj.2458
|View full text |Cite
|
Sign up to set email alerts
|

Effects of CO2laser irradiation on matrix-rich biofilm development formation–an in vitro study

Abstract: BackgroundA carbon dioxide (CO2) laser has been used to morphologically and chemically modify the dental enamel surface as well as to make it more resistant to demineralization. Despite a variety of experiments demonstrating the inhibitory effect of a CO2 laser in reduce enamel demineralization, little is known about the effect of surface irradiated on bacterial growth. Thus, this in vitro study was preformed to evaluate the biofilm formation on enamel previously irradiated with a CO2 laser (λ = 10.6 µM).Metho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…The media was changed daily without disrupting the biofilm on top of the disks. Biofilm was collected at days 2, 3, and 5 after surface treatment and later sonicated in 5 mL of phosphate-buffered saline (PBS) solution to obtain a homogenized solution (Murata et al, 2008;Salles Branco-De-Almeida et al, 2011;Zancopé et al, 2016).…”
Section: Biofilm Preparation and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The media was changed daily without disrupting the biofilm on top of the disks. Biofilm was collected at days 2, 3, and 5 after surface treatment and later sonicated in 5 mL of phosphate-buffered saline (PBS) solution to obtain a homogenized solution (Murata et al, 2008;Salles Branco-De-Almeida et al, 2011;Zancopé et al, 2016).…”
Section: Biofilm Preparation and Analysismentioning
confidence: 99%
“…The numbers of colonies were normalized and converted into Log 10 values for data interpretation. The CFU assay was performed in triplicate in at least three different experiments (Murata et al, 2008;Salles Branco-De-Almeida et al, 2011;Zancopé et al, 2016).…”
Section: Colony Forming Unitsmentioning
confidence: 99%
“…1 The preventive and therapeutic potential of the CO 2 laser for the inhibition of caries on enamel has been discussed. [2][3][4][5][6][7][8][9] However, the parameters for its most effective use are still under debate.…”
Section: Introductionmentioning
confidence: 99%
“…20 Although the literature is still sparse about the effect of the CO 2 laser on a dental biofilm, the equipment has been tested as an alternative to reduce oral bacterial infections. 2,4,13,21,22 Studies have shown its effectiveness against microorganisms that cause inflammation and dental caries. 4,13,21,22 The main mechanism of the bactericidal effect of the laser is the instantaneous vaporization of the intracellular water.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation